Administrative delegation and its impact on job performance in food factories in Qatar - AbdulRahman, AbdulRahman Yusuf (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to identify the impact of Administrative delegation on the job performance of Food factories in Qatar, determining the reality of Administrative delegation at Marikh Food factory in Qatar, the researcher used the Analytical descriptive curriculum in his study because of this is the most appropriate way for the study`s objectives, the samples of the study consisted of (150) employees working at Marikh Food factory in Qatar, and the study`s tool (Identification) was distributed to them, the study discovered a strong positive relationship of statistical significance to administrative delegation over job performance in Marikh Food factory in Qatar, and the reality of administrative delegation at Marikh Food factory in Qatar came at a high level with a general average is equal (3.94), and the reality of the job performance at Marikh Food factory in Qatar came at a high level with a general average is equal (3.76), the Results showed that the participation of all levels in the administrative hierarchy in the decisions-making helps to improve the job performance of Marikh Food factory in Qatar, and all leaderships’s types helped in support collaboration and the work participation, which helping in improve the job performance and achieve all of organization`s objectives which the organization aims to achieve it, the study`s recommendations areBasic training is necessary for all employees on administrative work and taking the responsibilityAnd encourage all employees for participate in the process of making decisions for improve the interaction in the working environment.
Keywords: Job performance; administrative delegation; Marikh Food factory; leadership styles; organization; interaction